2016
DOI: 10.1007/s13280-016-0850-1
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries regulatory regimes and resilience to climate change

Abstract: Climate change is already producing ecological, social, and economic impacts on fisheries, and these effects are expected to increase in frequency and magnitude in the future. Fisheries governance and regulations can alter socio-ecological resilience to climate change impacts via harvest control rules and incentives driving fisher behavior, yet there are no syntheses or conceptual frameworks for examining how institutions and their regulatory approaches can alter fisheries resilience to climate change. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 99 publications
(155 reference statements)
1
59
0
Order By: Relevance
“…Notwithstanding the importance of the ecosystem services provided by coastal regions, increasing evidence indicates that coastal ecosystems have been deeply altered, thus reducing their productivity and resilience (Jackson et al 2001, Ojea et al 2017. Such effects have intensified conflicts over resources (Prestrelo and Vianna 2016), thereby affecting social-ecological vulnerability in coastal areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the importance of the ecosystem services provided by coastal regions, increasing evidence indicates that coastal ecosystems have been deeply altered, thus reducing their productivity and resilience (Jackson et al 2001, Ojea et al 2017. Such effects have intensified conflicts over resources (Prestrelo and Vianna 2016), thereby affecting social-ecological vulnerability in coastal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Fishery nursery areas, e.g., coral reefs and mangroves, in Brazil have been affected by many human threats, such as coastal development, pollution, deforestation, and, again, climate change (Prates et al 2012). Some predictions have suggested that 40% of Brazilian reefs are at a high risk of declining in the very short term (Rodríguez-Ramírez et al 2008). Estuarine environments, which support relevant ecological functions, are considered to be the most threatened coastal ecosystems in the Brazilian marine ecoregions (Bernardino et al 2015, Sunday et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, such measures have contributed to dramatic declines in overfishing, increases in biomass, and maintenance of catch and profits [42]. In lower capacity systems, best practices include implementing “primary fisheries management” [43] that uses best available science and precautionary principles to manage data-poor and capacity-limited fisheries and establishing local, rights-based management [39] to incentivize sustainable stewardship. Rights-based management systems include catch share programs such as Individual Transferable Quotas (ITQs) and Territorial Use Rights in Fisheries (TURFs) that define property rights over catch and space, respectively [44].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of climate change on fishing communities can be reduced through measures that increase socioeconomic resilience and adaptive capacity to environmental variability and changing fisheries [40,64,65]. Across low to high capacity systems, these measures include (1) policies that facilitate flexibility, such as diversification of access to fisheries and alternative livelihoods, (2) policies that provide better assets, such as the enhancement of fisheries technology and capacity, (3) policies that provide better organization in the system, including multi-level governance, community-based management, and other governance structures [14, 39], and (4) policies that promote agency and learning [40]. For example, policies that promote access to multiple fisheries provide fishers with a portfolio of fishing opportunities that can buffer against variability [66, 67] while policies that promote diverse livelihoods reduce reliance on fisheries [68, 69].…”
Section: Discussionmentioning
confidence: 99%
“…• Qualitative criteria-based assessment, in which criteria are typically normative and drawn from social-ecological systems resilience framework and assessment is based on categorical scoring, such as presence/absence -for example, see Ojea et al (2017). • Semi-quantitative criteria-based assessment, in which criteria are more typical of those used in formative evaluation techniques, such as feasibility and risk, and assessment is based on ordinal scoring of criteria (i.e., ranking or Likert scale) -for example, see Marshall et al (2010).…”
Section: Introductionmentioning
confidence: 99%